Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve [tex]\(\sqrt[4]{3} \times \sqrt[4]{27}\)[/tex], we need to simplify and combine the expressions step-by-step. Follow along carefully:
1. Expressing both terms using fractional exponents:
[tex]\[ \sqrt[4]{3} = 3^{1/4} \][/tex]
[tex]\[ \sqrt[4]{27} = 27^{1/4} \][/tex]
2. Rewrite 27 using its prime factorization:
[tex]\[ 27 = 3 \times 3 \times 3 = 3^3 \][/tex]
Substituting in this factorization, we get:
[tex]\[ \sqrt[4]{27} = (3^3)^{1/4} \][/tex]
3. Applying the power of a power property [tex]\((a^{m})^n = a^{m \times n}\)[/tex]:
For the expression [tex]\((3^3)^{1/4}\)[/tex]:
[tex]\[ (3^3)^{1/4} = 3^{3 \times (1/4)} = 3^{3/4} \][/tex]
4. Now substitute back into our original expression:
[tex]\[ \sqrt[4]{3} \times \sqrt[4]{27} = 3^{1/4} \times 3^{3/4} \][/tex]
5. Using the property of exponents [tex]\((a^m \times a^n = a^{m+n})\)[/tex] to combine the terms:
[tex]\[ 3^{1/4} \times 3^{3/4} = 3^{1/4 + 3/4} \][/tex]
Simplify the exponent:
[tex]\[ 1/4 + 3/4 = 4/4 = 1 \][/tex]
So we have:
[tex]\[ 3^1 = 3 \][/tex]
Hence, the simplified result of [tex]\(\sqrt[4]{3} \times \sqrt[4]{27}\)[/tex] is [tex]\(3\)[/tex].
To provide the intermediate results from each step in numerical form:
- [tex]\(\sqrt[4]{3} \approx 1.3160740129524924\)[/tex]
- [tex]\(\sqrt[4]{27} = (3^3)^{1/4} \approx 2.2795070569547775\)[/tex]
- The product [tex]\(1.3160740129524924 \times 2.2795070569547775 \approx 2.9999999999999996\)[/tex]
Thus, the final result is [tex]\(3\)[/tex].
1. Expressing both terms using fractional exponents:
[tex]\[ \sqrt[4]{3} = 3^{1/4} \][/tex]
[tex]\[ \sqrt[4]{27} = 27^{1/4} \][/tex]
2. Rewrite 27 using its prime factorization:
[tex]\[ 27 = 3 \times 3 \times 3 = 3^3 \][/tex]
Substituting in this factorization, we get:
[tex]\[ \sqrt[4]{27} = (3^3)^{1/4} \][/tex]
3. Applying the power of a power property [tex]\((a^{m})^n = a^{m \times n}\)[/tex]:
For the expression [tex]\((3^3)^{1/4}\)[/tex]:
[tex]\[ (3^3)^{1/4} = 3^{3 \times (1/4)} = 3^{3/4} \][/tex]
4. Now substitute back into our original expression:
[tex]\[ \sqrt[4]{3} \times \sqrt[4]{27} = 3^{1/4} \times 3^{3/4} \][/tex]
5. Using the property of exponents [tex]\((a^m \times a^n = a^{m+n})\)[/tex] to combine the terms:
[tex]\[ 3^{1/4} \times 3^{3/4} = 3^{1/4 + 3/4} \][/tex]
Simplify the exponent:
[tex]\[ 1/4 + 3/4 = 4/4 = 1 \][/tex]
So we have:
[tex]\[ 3^1 = 3 \][/tex]
Hence, the simplified result of [tex]\(\sqrt[4]{3} \times \sqrt[4]{27}\)[/tex] is [tex]\(3\)[/tex].
To provide the intermediate results from each step in numerical form:
- [tex]\(\sqrt[4]{3} \approx 1.3160740129524924\)[/tex]
- [tex]\(\sqrt[4]{27} = (3^3)^{1/4} \approx 2.2795070569547775\)[/tex]
- The product [tex]\(1.3160740129524924 \times 2.2795070569547775 \approx 2.9999999999999996\)[/tex]
Thus, the final result is [tex]\(3\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.